2015
DOI: 10.1002/arco.5047
|View full text |Cite
|
Sign up to set email alerts
|

Innovation, adaptation and technology as habitus: the origins of alluvial gold mining methods in Australia

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
(45 reference statements)
0
2
0
Order By: Relevance
“…One example of technological innovation's role in migration is the adoption of mining techniques from Cornwall during the Australian gold rush, which occurred in 1851. These cutting-edge techniques relied extensively on dependable water sources, so miners created advanced technical and legal mechanisms to control the water supply to ensure their success [60][61][62]. Special techniques are involved using bucket dredging and hydraulic sluicing pumps and puddlers (ring-shaped trough in the ground for puddling gold from auriferous clay) [63] (Figure 14).…”
Section: Gold Rushes Over the Worldmentioning
confidence: 99%
“…One example of technological innovation's role in migration is the adoption of mining techniques from Cornwall during the Australian gold rush, which occurred in 1851. These cutting-edge techniques relied extensively on dependable water sources, so miners created advanced technical and legal mechanisms to control the water supply to ensure their success [60][61][62]. Special techniques are involved using bucket dredging and hydraulic sluicing pumps and puddlers (ring-shaped trough in the ground for puddling gold from auriferous clay) [63] (Figure 14).…”
Section: Gold Rushes Over the Worldmentioning
confidence: 99%
“…In these countries, assimilation and ANT are important foundations for the innovation process. Other studies have shown that in certain cases, information, system adoption, technological transfer and ANT are necessary for innovation (George and Lin, 2017;Lawrence and Davies, 2015). According to Lawrence and Davies (2015), small, initially marginal innovations and technological adaptations open up new opportunities and stimulate greater IP, then:…”
Section: Adoption Of New External Technologiesmentioning
confidence: 99%